The Feasibility Investment of Honey Bee Cultivation Business Trigona sp. in Landono District South Konawe Regency (Case Study of Madu Mas Forest Farmer Group) - Ahsan Taqwim Hasyim; Azhar Bafadal; Samsul Alam Fyka (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2022)
This study aims to analyze the financial aspects and the sensitivity of the Trigona sp. honey bee cultivation business in the Landono District, South Konawe Regency. This research was conducted from September 2021 to March 2022 using the case study method in the Madu Mas forest farmer group, with eight people used as informants. Research variables include informant identity and business feasibility analysis. The data analysis used is a quantitative analysis using investment assessment criteria including NPV, Net B/C, IRR, Payback Period, and sensitivity analysis. The results showed that the financial aspect obtained an NPV value of IDR40,139,762, with a discount factor of 14%, Net B/C of 1.94, an IRR value of 28.84%, and a Payback Period of 3 years four months so that the honey bee cultivation business declared financially viable. Based on the sensitivity analysis, the business is still feasible to run despite a 25% decrease in honey production and a 35% increase in operating costs. However, if there is a decrease in honey production by 25% and an increase in operational costs by 35% simultaneously, then the honey bee cultivation business is not feasible.